Імітаційне моделювання програми руху магістрального автопоїзда в транспортному потоці - Прокудін, Георгій; Оліскевич, Мирослав (Посвіт, 2019)
The paper studies the springiness of speeding traffic in terms of glare. Blindness occurred in the nighttime and carried automobile headlights at oncoming vehicles separation on two-lane road.
The simulation of truck desired travelling program of highway traffic
Keywords: 656.073.5; 629.058